Analisis kesalahan berbahasa tataran sintaksis pada pidato Presiden Jokowi dalam Sidang Umum PBB - Debi, Fanesia; Riyaningrum, Latifah; Dewi, Luthfiana Yunita; Ulya, Chafit (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2021)
The purpose of this research is (1) to describe the speaking errors in terms in the syntax on a speech the President Jokowi of the UN general assembly contained in the portal news Kompas.com Edition 23 September 2020 (2) to provide improvements in the syntax to the speech of the President Jokowi of the UN general assembly contained in the portal news Kompas.com Edition of 23 December 2020. This research is descriptive qualitative research. The data techniques used is the technique of intensive reading and technique of note. The results of the error in terms of the syntax show that the error in terms most found on the type of error the use of excessive or redundant. In addition, there is also a type of error in another language i.e. the use of prepositions that is not appropriate,Â  a double, the omission of conjunctions, the use of conjunctions excessive, and the use of foreign terms